Efektivitas Pesan Politik dalam Membangun Citra Kandidat: Studi terhadap Pemilih Muda - Mochammad Zaini; Ramziya Amjad Bakhitah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the effectiveness of political messages in building a candidate's image among young voters. In an election context that is increasingly dominated by technology and social media, appropriate political messages have an important role in shaping the views and choices of young voters. This study uses a qualitative approach with interviews and surveys as data collection methods, focusing on how young voters receive and respond to political messages conveyed by candidates. The findings of this research indicate that political messages that are relevant, authentic, and touch on issues close to the lives of young voters tend to be more effective in building a positive image of candidates. The research results also reveal that social media plays a significant role in amplifying political messages, with young voters more exposed to messages that are packaged visually and interactively. Young voters tend to choose candidates who are able to adapt to technological developments and communicate their vision directly and transparently. Therefore, candidates who are successful in managing their political messages on various digital platforms have a great opportunity to improve their image and attract the attention of young voters. This research contributes to understanding the dynamics of political communication in the digital era, as well as the importance of appropriate communication strategies in gaining the support of young voters.